Entrepreneurship and Philippine development - Batalla, Eric Vincent C. (Animo Repository, 2010)
Assessments of Philippine development performance raise questions about the quantity and quality of Filipino entrepreneurship. Despite the early attempt at industrialization, industrial entrepreneurship has failed to flourish in the country. Is industrial entrepreneurship constrained more by cultural limitations than by political and economic factors? This paper provides a brief historical survey of Philippine entrepreneurship and development. It argues that Philippine industrial entrepreneurship did not take off because of a combination of external constraints and internal motivations. © Revue canadienne d'études du développement, 2010. Tous droits réservé s.